Assessment of experiences of survivors of cerebro-vascular accidents and their caregivers functioning at home in the Oshana region of Namibia - Kuugongelwa, Suama; Small, Louis F (International Journal of Advanced Nursing Studies, 2015)
In the wake of a cerebro-vascular accident, survivor and caregiver are often apprehensive about being on their own at home; this is particularly so for those living in low socioeconomic circumstances in the rural areas of Namibia. The situation is aggravated by the fact that there is no structured system of home visits by health workers that could assist caregivers in their daily tasks. Phenomenological interviews were therefore conducted to explore how these caregivers cope with providing home care to the survivors of such accidents. The findings that emerged were categorised into four themes, namely, survivors were unable to provide self-care and were dependent on others for help, the altered role function and performance of survivors, negative emotions because of altered self-esteem, and disrupted social interaction. These experiences together illustrate that some survivors are unable to take care of themselves at all and depend completely on their caregivers for help.